PENINGKATAN TECHNOPRENEURSHIP SKILL PELAKU UMKM DAN PELATIHAN OPTIMALISASI TEKNOLOGI SISTEM VIRTUAL BANKING DALAM E-COMMERCE - Saut Pintubipar Saragih; Irene Svinarky; Tiur Niari Purba (ASOSIASI IDEBAHASA KEPRI, 2026)
The development of the digital economy requires MSME actors, including PKK community groups, to possess technopreneurship skills and the ability to utilize digital payment systems. However, limited technological literacy and digital banking competence remain major challenges. This community service program aims to enhance technopreneurship understanding and skills, as well as to optimize the use of digital banking through Virtual Account (VA) features in e-commerce transactions among the PKK group of Puri Rhabayu, Batam City. The program was implemented using a participatory and practical approach through face-to-face training sessions, conceptual material delivery, technical skill training, e-commerce transaction simulations, and hands-on practice mentoring. The training materials covered technopreneurship concepts and types, the utilization of e-commerce platforms, basic digital marketing strategies, and the use of Virtual Accounts in online buying and selling transactions. The results indicate a significant improvement in participants’ technopreneurship understanding, digital banking literacy, and ability to independently conduct e-commerce transactions using Virtual Accounts. In addition, the program increased entrepreneurial motivation, production creativity, and awareness of legal aspects related to digital transactions. Overall, this program was considered successful and has strong potential for sustainable development in technology-based community economic empowerment.